INNOVATIVE TECHNOLOGIES IN CARDIOLOGY: FROM SURPRISE TO HABIT OR FORGETFULNESS - S. R. Gilyarevskiy; M. V. Golshmid; I. M. Kuz'mina (Рациональная фармакотерапия в кардиологии, 2015)
Change of the status of innovative technologies depending on the received evidences is considered. Examples reflecting the initiation of interest in the new technology of treatment, the transition from innovation to standard therapies, as well as the weakening of interest in the previously introduced technology due to disappointing results of clinical trials on evaluation of its effectiveness are presented.